INVESTIGATING METACOGNITIVE LISTENING STRATEGY AND LISTENING PROBLEMS ENCOUNTERED BY ENGLISH LEARNERS - Sarita Merilia (Universitas Pamulang, 2019)
Abstract Among listening strategies that are proposed by experts, metacognitive is one of important strategies in language learning. Metacognitive strategies help students understand the way they learn and the steps they take. Hence, learners will success in learning a language. The study investigated metacognitive listening strategies awareness and the listening difficulties among the second semester students at Faculty of Letter of Universitas Pamulang academic year 2017/2018. Out of 300 students of the population, 131 students (99 females and 32 males) were chosen as the samples based on the random sampling. The data in this study were obtained through questionnaires (MALQ, Vandergrift et al, 2006) and openended questionnaire. This study revealed that overall the highest level of the students’ metacognitive awareness is problem solving and the lowest is directed attention. The students identified a number of factors that contribute to difficulties in listening comprehension: lack of vocabulary, speaker speed, accent, pronunciation, concentration, and other problems. In this paper, the findings and conclusion are discussed for classroom instruction and note substantive concerns that should be addressed in future research. Keywords: English learners, listening problem, listening skill, metacognitive, strategy